1985
DOI: 10.2165/00003495-198529040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Ceftizoxime A Review of its Antibacterial Activity, Pharmacokinetic Properties and Therapeutic Use

Abstract: Ceftizoxime is a 'third generation' cephalosporin administered intravenously or intramuscularly. Like other third generation cephalosporins it has a wide spectrum of in vitro activity against Gram-positive and Gram-negative bacteria, is particularly active against Enterobacteriaceae (including beta-lactamase-positive strains), and is resistant to hydrolysis by beta-lactamases. However, the third generation cephalosporins are less active than earlier cephalosporins against staphylococci and so could not be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 129 publications
11
89
0
2
Order By: Relevance
“…The levels of cefepime in plasma increase in a dose-proportional manner, and dose-independent parameters such as MRTiV, t112, CL., CLE, and Vs remained constant from the 250-to the 2,000-mg dose. These findings are consistent with those reported for other cephalosporins such as ceftazidime (16,26), cefpirome (21,22), cefpiramide (23), and cefotetan (24). The Cm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The levels of cefepime in plasma increase in a dose-proportional manner, and dose-independent parameters such as MRTiV, t112, CL., CLE, and Vs remained constant from the 250-to the 2,000-mg dose. These findings are consistent with those reported for other cephalosporins such as ceftazidime (16,26), cefpirome (21,22), cefpiramide (23), and cefotetan (24). The Cm.…”
Section: Discussionsupporting
confidence: 89%
“…It is likely that the CLR of cefepime, like that of ceftazidime (16,26), occurs by glomerular filtration, with negligible tubular secretion (1,3,5). A drug disposition study using radiolabeled cefepime clearly indicated that this cephalosporin undergoes minimal metabolism and is excreted primarily as an unchanged drug in urine in humans with normal kidney functions (4).…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime has its primary affinity for PBP 3 at low concentrations (14). We found short PAEs and mainly filaments for ceftazidime at up to 16 times the MIC.…”
Section: Resultsmentioning
confidence: 54%
“…We found short PAEs and mainly filaments for ceftazidime at up to 16 times the MIC. At higher concentrations of the drug, it also has affinities for PBP la and PBP lb (14). At 64 times the MIC and at higher concentrations, we observed PAEs of at least 2 h and a morphology of predominantly spheroplasts.…”
Section: Resultsmentioning
confidence: 65%
“…It is well-described that ceftazidime displays timedependent pharmacodynamic activity requiring approximately 60% time above MIC for efficacy (33,34). However, the question of avibactam dosing frequency needed further elucidation.…”
Section: Pharmacodynamicsmentioning
confidence: 99%